Video-monitoring techniques and methodological approaches to improve the wave run-up computattion Mira beach, Portugal - Γιαννουκάκου-Λεοντσίνη, Ιφιγένεια (2021)
Submitted project to the University of Aveiro and University of the Aegean in order to ingrate the degree in Marine Sciences under the supervisions of Professor Paulo Manuel Cruz Alves da Silva and Professor Joaquim Pais Barbosa